Women governance and politics - Subhash Chandra (Jaipur Book Enclave, 2020)
Introduction; politics and administration representation of women; womens participation by villagers in panchayat activities; importance of womens education for national life; women changing the good governance; womens right and its obstacles; empowering women and labour market structure.
Keywords: Social Change